2022
DOI: 10.3389/fimmu.2022.982773
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of lncRNAs in osteoarthritis: An updated review

Abstract: Osteoarthritis (OA) is a prevalent joint disease, which is associated with progressive articular cartilage loss, synovial inflammation, subchondral sclerosis and meniscus injury. The molecular mechanism underlying OA pathogenesis is multifactorial. Long non-coding RNAs (lncRNAs) are non-protein coding RNAs with length more than 200 nucleotides. They have various functions such as modulating transcription and protein activity, as well as forming endogenous small interfering RNAs (siRNAs) and microRNA (miRNA) sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 206 publications
0
7
0
1
Order By: Relevance
“… 27 Recently, accumulating evidence indicated that lncRNA dysregulation plays important roles in OA progression by cartilage degradation, synovial inflammation, and dysfunction of subchondral bone homeostasis and that lncRNAs could serve as therapeutic targets. 28 , 29 , 30 Therefore, an expanded understanding of the functions and regulatory mechanisms of lncRNAs in OA may provide potential therapeutic targets for OA.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Recently, accumulating evidence indicated that lncRNA dysregulation plays important roles in OA progression by cartilage degradation, synovial inflammation, and dysfunction of subchondral bone homeostasis and that lncRNAs could serve as therapeutic targets. 28 , 29 , 30 Therefore, an expanded understanding of the functions and regulatory mechanisms of lncRNAs in OA may provide potential therapeutic targets for OA.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that lncRNA H19 is an important lncRNA in the pathogenesis of OA. One of these studies showed that knockdown of lncRNA H19 alleviated apoptosis and inflammation by sponging miR130a in LPS-stimulated human C28/I2 chondrocytes ( 99 , 100 ), and studying the combination of these drugs with nonsteroidal anti-inflammatory drugs is highly important for targeted treatment.…”
Section: Lncrna-related Therapymentioning
confidence: 99%
“…GAS5, which is involved in GR activity, is a lncRNA of great interest to researchers in recent years ( 102 ). GAS5 is an important lncRNA in OA patients ( 99 ). GAS5 is downregulated in OA patients mainly in articular cartilage tissues and synovial cells.…”
Section: Lncrna-related Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs with longer than 200 nucleotides have been identified to involve in diverse diseases via regulating gene expression and chromatin remodeling, including cancer, neurodegenerative diseases and cardiovascular disorders ( Jiang et al, 2020 ; Cheng et al, 2022 ; Gareev et al, 2022 ; Sufianova et al, 2022 ; Xie et al, 2022 ). LncRNAs have gained significant attention and play crucial regulatory roles in osteoarthritis ( Chen et al, 2017 ; Abbasifard et al, 2020 ; Tu et al, 2020 ; Wang et al, 2022 ; Okuyan and Begen, 2022 ). In this review, we will describe the role of numerous lncRNAs in osteoarthritis development and progression.…”
Section: Introductionmentioning
confidence: 99%